Material world 3 innovative materials for architecture and design - Ternaux, Elodie (Frame Publishers, 2011)
"In this book materio also summarizes fifteen basic concepts to help novices gain a better understanding of this complex topic and to point out, even to the more well-informed reader, aspects of materials that are often overlooked. What do FSC, VOC, cradle to cradle, and oxo-degradable mean? What are Damask steel, float glass, and electroluminescence? What's the story behind the invention of nylon, or of Velcro? Find the answers to these and many other relevant questions in this book. Taken as a whole, these features make Material World 3 a virtually encyclopedic survey of exciting materials and finishes for use in interior design and architecture." -- Provided by publisher